Spatio-temporal variation of oasis landscape pattern in arid area: Human or natural driving? - Changjiang Liu (Elsevier, 2021)
The eco-environment of the arid area is constantly fragile global-wide. The study on the spatial and temporal variation of its landscape pattern can quickly identify the driving factors, which is an effective analysis method of ecological conservation in the arid area. In this study, Jinghe County, Xinjiang, in Northwestern China, is chosen as a case study of understanding the major driving force of the oasis landscape. Landsat satellite images of 1994, 2007, and 2017 are used as the basic data sources for analysis. The moving window method, transition matrix, and factor analysis are selected as the main technical means for this paper to reveal the temporal and spatial variation of landscape pattern in Jinghe County, and to quantitatively describe its driving factors. The results of the analysis show that: (1) The landscape pattern of Jinghe County has changed dramatically, especially the construction land and farmland. Both show an increase of 351.29% and 269.01% respectively between 1994 and 2017. Farmland increased the most, with the proportion of 6.45% in Jinghe County, and expanded along with the “triangle” three sides. The area of forest land increased slightly, the area of grassland and unused land decreased, and the area of water did not change significantly. (2) The dominant obvious regional differences of landscape types in Jinghe County are mainly manifested in farmland and forest land. Taking the unused land as the boundary, the biodiversity of farmland decreased, and the aggregation degree deepened, while the fragmentation degree of forest land increased. (3) The spatial–temporal variation of landscape patterns in Jinghe County is the result of the combination of natural and human factors, but the correlation between human factors and the change of landscape area is significantly greater than that of natural factors. Thus, human factors are the main driving force of landscape pattern change in Jinghe County. The scientific management and planning of the intensity of human activities in Jinghe County should be the focus of ecological environment restoration and protection.